Resection of Distal Radius Giant Cell Tumor and Reconstruction with Non-Vascularized Fibular Graft: A Case Report - Kambey, Stefan A. G. P.; Rawung, Rangga B. V.; Christorei, Tooy D. (Medical Scope Journal, 2025)
Abstract: Giant cell tumor (GCT) is a benign and locally aggressive tumor. Cases of GCT found at the distal radius were rare and difficult to control locally. We reported a case of GCT with en bloc resection and reconstruction using non-vascularized fibular autograft. A 57-year-old female patient presented with a lump on the wrist joint of left arm, and was confirmed to have a giant cell tumor by histological study. The tumor was classified as a Campanacci Grade III tumor, therefore, an en bloc resection with non-vascularized fibular autograft was performed. Arthrodesis was added to increase stability. Resection with a clear margin, with no complications, was possible despite not previously receiving downsizing neoadjuvant chemotherapy. Acceptable functional results were achieved postoperatively; however, wrist motion was reduced due to the arthrodesis. Long-term follow-up should consider recurrence and graft-related complications, including fractures, dislocations, or subluxations. In conclusion, while there is no general consensus of how to treat GCT, the Campannaci classification is useful to make a surgical decision. Resection and reconstruction with non-vascularized fibular autograft were satisfactory, having achieved free margin resection. However, there is a decreased range of motion due to arthrodesis of wrist, in order to prevent subluxation and dislocation. Long term follow up is necessary to observe recurrences and complications related to bone autograft utilization. Keywords: giant cell tumor; fibular graft; distal radius; reconstruction